Kekhususan Substrat Lipase Miselium Rhizopus oryzae - Salleh, Abu Bakar; Wan Yunus, Wan Md Zin; Basri, Mahiran; Ampon, Kamaruzaman; Abdul Razak, Che Nyonya (Universiti Putra Malaysia Press, 1996)
The substrate specificity of a mycelial lipase from Rhizopus oryzae for the esterification reaction was investigated. Studies showed that the enzyme exhibited high activity when long-chain fatty acids (Cl2-Cl8) were reacted with primary alcohols (C3-C7) as well as primary diols. The presence of double bonds did not affect reactions significantly, but esterification activity for secondary, tertiary or aromatic alcohols was low.